Validation of intra-operative parathyroid hormone and its decline as early predictors of hypoparathyroidism after total thyroidectomy: A prospective cohort study. (June 2015) - Gupta, Shailesh; Chaudhary, Poras; Durga, Chikkala K.; Naskar, Dipankar
Abstract: Introduction: Total thyroidectomy is a preferred surgical technique for benign as well as malignant thyroid pathologies, but many a times can cause hypoparathyroidism. The aim of this study is to evaluate the intra-operative parathyroid hormone (ioPTH) level and its decline as predictors for post-operative hypoparathyroidism after total thyroidectomy. Methods: In this single-centre prospective cohort study, 90 patients who underwent total thyroidectomy for benign as well as malignant pathologies of thyroid gland were studied. Intra-operative parathyroid levels and at different time intervals parathyroid hormone and serum calcium levels were measured to predict hypoparathyroidism. The data was analysed using independent sample t test and p value < .05 was considered to be significant. Results: There were 14 male and 76 female patients with a mean age of 41 years. Most common thyroid pathology for which total thyroidectomy was done was colloid goitre (62). Twenty four patients (26.66%) developed hypoparathyroidism. Intra-operative PTH was found to be most accurate predictor for diagnosing post-operative hypoparathyroidism (cut off was (11.3 pg/ml, calculated using ROC curves) and has maximum sum of sensitivity (91.7%) and specificity (97%). On taking cut off values of intra-operative PTH and PTH decline together, they were found to be most accurate predictor for permanent hypoparathyroidism. Discussion: Early and accurate predictor of hypoparathyroidism is very important and always sought. Very early prediction during intra-operative periods can be used for auto transplantation of parathyroid gland. Conclusion: Intra-operative parathyroid hormone and its decline are accurate, reliable, and early predictor of hypoparathyroidism after total thyroidectomy. Highlights: Hypoparathyroidism is a common complication after total thyroidectomy. Early and accurate predictor of hypoparathyroidism is always sought. ioPTH and PTH decline are accurate, reliable, and early predictor of post-operative hypoparathyroidism.